Preparação da Liga Amorfa Co72Nb24B4 como Catalisador na Reação de Oxidação do Metanol - Nascimento, Luciano; Rodbari, Reza Jamshidi; Barbosa, Celmy Maria B. de Menezes; Melnyk, Anastasiia; Jamshidi, Lourdes Cristina L. A. (Orbital: The Electronic Journal of Chemistry, 2015)
This study aims to investigate and characterize the amorphous alloy Co72Nb24B4 the catalytic oxidation of methanol in products that serve as primary reagents for organic synthesis, such as formaldehyde and other intermediate products. The technique for obtaining the amorphous alloy was electric arc smelting furnace. The amorphous alloy catalyst Co72Nb24B4 was characterized by XRD, SEM / EDS, BET and thermal analysis TGA and DTA. The objective of this work is to develop and study the application of amorphous alloy as catalysts and catalyst supports, due to its thick this oxide layer on its surface capable of oxidizing methanol and intermediates of methanol oxidation reaction. The amorphous alloy structure Co72Nb24B4 is still stable after the catalytic test, since the formation of intermetallic and amorphous phases are rich in active sites that are important for the catalytic processes at the surface of these amorphous materials. DOI: http://dx.doi.org/10.17807/orbital.v7i4.768